Exploring the link between diet and sustainability in Europe: A focus on meat and fish consumption - Diana Kmetkova; Milan Scasny; Iva Zverinova; Vojtech Maca (Charles University in Prague, Institute of Economic Studies (IES), 2023)
Global food production practices and consumption patterns have changed notably in the last few decades. Current dietary patterns are characterized by increased consumption of refined sugars as well as higher intakes of heavily-processed and animal-source foods, which results in higher obesity rates and increased prevalence of diet-related non-communicable diseases. Moreover, diets high in animal products are associated with a larger environmental burden. The aim of this paper is to examine the association between the consumption of meat and fish and economic and socio-demographic factors, different consumption habits and behaviours of individuals in five European countries. Using household-level data, descriptive analysis is presented and regressions using Heckman's standard sample selection model are conducted. The main reasons for not eating meat or fish are ethics, environment, taste and health. Our findings also suggest that though income results to be significant, its positive effect on meat and fish intake is rather small. Regarding fish, the price of groceries seems to have a significant negative impact while it does not affect the consumption of white meat. This indicates that if we want to lower the consumption of (especially red) meat, we should focus on other factors, such as gender, age, healthy habits and behavioural traits or values (especially factors that are part of the decisionmaking process during food purchases like price, taste, habit, family and appearance). Moreover, meat and fish intakes differ significantly among analysed countries, hence, the policy recommendations should be based on a local context.
Keywords: C34; C38; I15; O12; O13; Q56; 330; income; meat and fish consumption; animal protein; healthy and sustainable diet; behavioural analysis